In Vivo Evaluation of the Skin Tensile Strength by the Suction Method: Pilot Study Coping with Hysteresis and Creep Extension. (5th August 2013) - Piérard, Gérald E.; Piérard, Sébastien; Delvenne, Philippe; Piérard-Franchimont, Claudine
Abstract : From an engineering standpoint, both the skin and subcutaneous tissue act as interconnected load-transmitting structures. They are subject to a variety of intrinsic and environmental influences. Changes in the cutaneous viscoelasticity represent an important aspect in a series of skin conditions. The aim of this work was to explore the methodology of biomechanical measurements in order to better appreciate the evolution and severity of some connective tissue diseases. The Cutometer MPA 580 (C+K electronic) was used in the steep and progressive suction procedures. Adapting measurement modalities was explored in order to mitigate any variability in data collection. The repeat steep suction procedure conveniently reveals the creep phenomenon. By contrast, the progressive suction procedure highlights the hysteresis phenomenon. These viscoelastic characteristics are presently described using the 2 and 4 mm probes on normal skin and in scleroderma, acromegaly, corticosteroid-induced dermatoporosis, and Ehlers-Danlos syndrome. The apposition of an additional outer contention on the skin altered differently the manifestations of the creep extension and hysteresis among the tested skin conditions. Any change in the mechanical test procedure affects the data. In clinical and experimental settings, it is mandatory to adhere to a strict and controlled protocol.